Regionalization of health in Brazil: an analytical perspective - Duarte, Ligia Schiavon; Pessoto, Umberto Catarino; Guimarães, Raul Borges [UNESP]; Heimann, Luiza Sterman; Carvalheiro, José da Rocha; Cortizo, Carlos Tato; Ribeiro, Eduardo Augusto Werneck (Univ Sao Paulo, Fac Saude Publica, 2015)
This article aims to contribute to the debate on the SUS regionalization policy and the establishment of health regions in Brazil. Understanding them require to recognize the dichotomy between public health and individual health - which marks the history of Brazilian public health - and identify the different rationalities that lead this process. Such rationalities allow not only to consider the legacy of municipalization in the current regionalization process, as well as to establish links between the two fields of fundamental knowledge to the debate, epidemiology and geography. Clinical epidemiology, privileging individual health, gives basis to a healthcare model that prioritizes the optimization of resources. The recognition of health in its broader concept, in the social epidemiology, bases an attention model aimed at social determinants. With geography, functional regions can be formulated, based on Christaller's theory, or lablachianas regions which recognize the social loco / regional structure, allowing intervention in determining or conditioning the way of illness and death of populations.

Este artigo visa a contribuir com o debate sobre a política de regionalização do SUS e a constituição das regiões de saúde no Brasil. Compreendê-las pressupõe reconhecer a dicotomia entre saúde coletiva e saúde individual – que marca a história da saúde pública brasileira – e identificar as diferentes racionalidades que conduzem esse processo. Tais racionalidades permitem não apenas considerar o legado da municipalização no atual processo de regionalização, como também estabelecer nexos entre dois campos do conhecimento fundamentais para o debate, a epidemiologia e a geografia. A epidemiologia clínica, ao privilegiar a saúde individual, fundamenta um modelo assistencial que prioriza a otimização de recursos. O reconhecimento da saúde no seu conceito ampliado, na epidemiologia social, fundamenta um modelo de atenção voltado para os determinantes sociais. Com a geografia, podem-se formular regiões funcionais, baseadas na teoria de Christaller, ou regiões lablachianas, que reconhecem a estrutura social loco/regional, possibilitando a intervenção nos determinantes ou condicionantes da maneira de adoecer e morrer das populações.
Keywords: Regionalization in health; Health regions; Municipalization in health; Brazilian national health system